Soil fungal community associated with peat in Sarawak identified using 18S rDNA marker - Ali, S.R.A.; Safari, S.; Thakib, M.S.; Bakeri, S.A.; Ghani, N.A.A. (Malaysian Palm Oil Board, 2016)
Fungi are principal decomposing microorganisms in acidic environment of peatlands. A useful tool for molecular screening of soil fungal communities using the 18S rDNA primer has been proven capable of identifying a broad range of fungi species within Ascomycota, Basidiomycota, Zygomycota and Chytridiomycota. Currently, very little information is available on fungal communities in deep peat of Sarawak, Malaysia. In this study, we have isolated the fungi from soil samples taken in deep peat forests and oil palm cultivated areas. The fungal identity was undertaken using 18S rDNA primer which is EF4-F/fung5-R. The microscopic structures were conducted to confirm the identity of the isolates. Based on this study, the fungal division most commonly found in deep peat is the Ascomycota. Aspergillus fumigatus was the most common species and more dominant in oil palm cultivated areas and logged-over forest than in primary forest. In the primary forest, the dominant species was the A. flavus, while Hypocrea atroviridis was commonly associated with oil palm cultivated areas and logged-over forest. Other species of fungi isolated in peat primary forests were Penicillium chrysogenum, Trichoderma sp., Phanerochaete sp., Mortierella chlamydospora, A. niger, A. alliaceus, etc. The in-depth difference in the fungal communities for the different sites will be further investigated using the next generation sequencing technology.